Older drivers : examinations of licensing procedures and driver skill evaluation - Horton, Catherine (New York : Nova Science Publishers, Inc., 2015)
The population of adults 65 and older is the fastest growing demographic in the United States. It is estimated that by 2030, drivers over 65 will represent a quarter of total driver fatalities. When comparing the crash rates per mile driven of various age groups, the data resemble a U-shaped curve. Young drivers have the highest crash rate, which drops as drivers leave their teens. After age 25, the crash rate remains low until around age 70 when it begins to increase again. This U-shaped trend on crashes per mile driven has been found in many studies in many countries. Given the increase in c.
9.2.1. Crash and Fatality Rate Profile9.3. Missouri; 9.3.1. Crash and Fatality Rate Profile; 9.4. Nebraska; 9.4.1. Crash and Fatality Rate Profile; 9.5. Vermont; 9.5.1. Crash and Fatality Rate Profile; 9.6. Wisconsin; 9.6.1. Crash and Fatality Rate Profile; 10. Comparison of Crash and Fatality Rates across States; 10.1. Crashes per 1,000 Licensed Drivers; 10.2. Crashes per 1,000 Population; 10.3. Driver Fatalities per 100,000 Licensed Drivers; 10.4. Driver Fatalities per 100,000 Population; 11. Discussion; 11.1. The Licensing Process; 11.2. Reactions of Older Drivers.
Includes index.
Keywords: Older automobile drivers; Drivers' licenses; Automobilistes âgés.; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Drivers' licenses; Older automobile drivers